Prospective Philosophical Foundations of Peace Education - McGregor, Sue (In Factis Pax: Journal of Peace Education and Social Justice, 2014)
There are many attributes of an effective peace educator,1 including having a philosophy of peace.2 And, while “a peace philosophy without practicability is imperfect and incomplete”, having no peace philosophy at all (or having an unexamined or unarticulated philosophy) is even worse. Its critical absence compromises a peace educator’s ability to formulate responses to life and reality. Educators who live life without a philosophy tend to act out their opinions without examining them, which is an untenable approach for peace educators.